A Simple Procedure for the Oxidation of Alcohols Using [Bis(acetoxy)iodo]benzene and a Catalytic Amount of Bromide Ions in Ethyl Acetate - Salvo, Anna Maria Pia; Campisciano, Vincenzo; Beejapur, Hazi Ahmad; Giacalone, Francesco; Gruttadauria, Michelangelo (Synlett, 2015)
Primary and secondary benzylic alcohols and secondary aliphatic alcohols were oxidized to the corresponding aldehydes and ketones by using [bis(acetoxy)iodo]benzene (BAIB) and a catalytic amount of bromide ions, from tetrabutylammonium bromide or KBr, in ethyl acetate. The catalytic role of the bromide ions was also highlighted in the oxidation of primary aliphatic alcohols and secondary allylic alcohols carried out in the presence of 1 mol% TEMPO.
Keywords: alcohols; aldehydes; catalysis; ketones; oxidation